PENGEMBANGAN MEDIA POSTER DIGITAL TERHADAP POTENSI DIRI SISWA KELAS VIII SMP NEGERI 2 PADALARANG - Pranata, Amelia Putri; Mustika, Ika; Septian, Muhammad Rezza (IKIP Siliwangi, 2023)
Humans are motivated to maintain life and continue to develop for the better. As well as self-potential, self-potential is very important to develop students' skills and abilities, while delivering information on self-potential using digital poster media as a means of information that can be accessed easily. This article aims to find out the feasibility of developing digital poster media on the potential of class VIII SMP NEGERI 2 Padalarang students, using the research & development (RnD) method, with one of the stages used, namely the validation stage. The subjects of this research were two counseling guidance lecturers from IKIP Siliwangi as media and material validators and counseling guidance teachers at SMPN 2 Padalarang. The instrument is a validation questionnaire with descriptive statistical analysis in the form of percentage descriptive. The results of the study show that the material expert's feasibility test is 96.66% in the very feasible category, the media aspect based on the expert validator is 96.42% in the very feasible category, and the media and material aspect based on the practitioner is 93% in the very feasible category. That way, all aspects that are assessed get a very worthy category to be tested on students.